2019
DOI: 10.1080/01616412.2019.1602312
|View full text |Cite
|
Sign up to set email alerts
|

Age and sex-mediated differences in six-month outcomes after mild traumatic brain injury in young adults: a TRACK-TBI study

Abstract: Risk factors for young adults with mTBI are not well understood. Improved understanding of age and sex as risk factors for impaired six-month outcomes in young adults is needed.Methods: Young adult mTBI subjects aged 18-39-years (18-29y; 30-39y) with six-month outcomes were extracted from the Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot (TRACK-TBI Pilot) study. Multivariable regressions were performed for outcomes with age, sex, and the interaction factor age-group*sex as variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 73 publications
4
43
1
Order By: Relevance
“…Besides outcome measures and TBI severity, there are other personal and clinical factors that could impact the results of sex/ gender-based analyses such as extracranial injuries or medical history, but these are often not included. 8,31 For instance, stratified analyses on both age and sex have shown that certain subgroups are at higher risk for developing poor outcomes following TBI, such as young women for post-traumatic stress disorder (PTSD), 34 women in ''child-bearing years'' for post-concussion symptoms (PCS), 35 and older women for mortality after isolated TBI. 36 Nevertheless, sex/gender differences in treatment and outcomes after TBI remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Besides outcome measures and TBI severity, there are other personal and clinical factors that could impact the results of sex/ gender-based analyses such as extracranial injuries or medical history, but these are often not included. 8,31 For instance, stratified analyses on both age and sex have shown that certain subgroups are at higher risk for developing poor outcomes following TBI, such as young women for post-traumatic stress disorder (PTSD), 34 women in ''child-bearing years'' for post-concussion symptoms (PCS), 35 and older women for mortality after isolated TBI. 36 Nevertheless, sex/gender differences in treatment and outcomes after TBI remain inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Pre-pubertal and pubertal females have increased ICU admissions and lengths of stay (LOS) (24); however, post-pubertal, perimenopausal, and postmenopausal women have lower hospital and ICU LOS than their male counterparts (25). Interestingly, adult men and women have different frequencies of post-concussive symptoms such as headache, dizziness, irritability, and insomnia, as well as in functional outcomes measured by the Glasgow Outcome Scales-Extended (GOS-E); however, this data has not yet been reported in children based on pubertal stage (27,28).…”
Section: Sex-related Differences In Overall Tbi Outcomesmentioning
confidence: 99%
“…A post-TBI study found that male sex increased risk of post-injury substance use disorder (96). Perimenopausal women have an increased susceptibility to psychiatric disorders following TBI such as depression and anxiety (28). Although there are many aspects predisposing patients to psychiatric disorders, reasons for sexually dimorphic psychiatric responses remain unclear.…”
Section: Neuropsychological Disturbancesmentioning
confidence: 99%
“…Post-traumatic stress disorder (PTSD) is a psychological disorder characterized by intense fear, helplessness, and avoidance, resulting from exposure to a traumatic event or catastrophic life event. It is clinically manifested with three main syndromes: re-experiencing, avoidance behavior or numbness, and physiological hyperarousal [10,11]. The current study used the post-traumatic checklist scale (PCLS-L) to measure the PTSD of MHD patients.…”
Section: Measuring Toolsmentioning
confidence: 99%